The Application of Benchmarking in Public Sector – Lessons from Germany - Fahlevi, Heru (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2015)
This study aims at evaluating the usefulness and exploring the problems/challenges and potential improvements of the application of benchmarking in German public sectors. It is a conceptual paper or literature review that discusses how benchmarking is adopted in Germany. The data ismainly collected from secondary sources i.e. articles, scientific research, non-governmental studies. The study uncovered that benchmarking application in a federal country has a peculiar challenges and problem that hindered an optimal utilization and benefit of the benchmarking adoption. Thus, lessons learned can be obtained for other countries in developing benchmarking in their administration.